Wearable multi-sensing double-chain thermoelectric generator - Wen, Dan-Liang; Deng, Hai-Tao; Liu, Xin; Li, Guo-Ke; Zhang, Xin-Ran; Zhang, Xiao-Sheng (Microsystems & nanoengineering, 2020)
Wearable electronics play a crucial role in advancing the rapid development of artificial intelligence, and as an attractive future vision, all-in-one wearable microsystems integrating powering, sensing, actuating and other functional components on a single chip have become an appealing tendency. Herein, we propose a wearable thermoelectric generator (ThEG) with a novel double-chain configuration to simultaneously realize sustainable energy harvesting and multi-functional sensing. In contrast to traditional single-chain ThEGs with the sole function of thermal energy harvesting, each individual chain of the developed double-chain thermoelectric generator (DC-ThEG) can be utilized to scavenge heat energy, and moreover, the combination of the two chains can be employed as functional sensing electrodes at the same time. The mature mass-fabrication technology of screen printing was successfully introduced to print n-type and p-type thermoelectric inks atop a polymeric substrate to form thermocouples to construct two independent chains, which makes this DC-ThEG flexible, high-performance and cost-efficient. The emerging material of silk fibroin was employed to cover the gap of the fabricated two chains to serve as a functional layer for sensing the existence of liquid water molecules in the air and the temperature. The powering and sensing functions of the developed DC-ThEG and their interactions were systematically studied via experimental measurements, which proved the DC-ThEG to be a robust multi-functional power source with a 151 mV open-circuit voltage. In addition, it was successfully demonstrated that this DC-ThEG can convert heat energy to achieve a 3.3 V output, matching common power demands of wearable electronics, and harvest biothermal energy to drive commercial electronics (i.e., a calculator). The integration approach of powering and multi-functional sensing based on this new double-chain configuration might open a new chapter in advanced thermoelectric generators, especially in the applications of all-in-one self-powered microsystems. Flexible electronics: energy harvesting and sensing A wearable thermoelectric device enables energy generation and sensing for health monitoring. Flexible electronic devices are promising candidates for personal health monitoring, and the ideal device would combine multiple functions in a single device. Two of the most important of these functions are energy generation and sensing. In this paper a team from University of Electronic Science and Technology of China led by Xiao-Sheng Zhang reports a thermoelectric-based device that combines these functions. Based on screen printing technology, they prepare n-type and p-type inorganic films onto a flexible polymer substrate, with their device being able to generate a voltage of up to 151 mV driven by a thermoelectric effect. The water sensitivity and temperature sensitivity of silk fibroin contained in the device enables moisture and temperature to be sensed.